CHANGES IN SYSTEMIC LEVELS OF VASCULAR ENDOTHELIAL GROWTH FACTOR AFTER INTRAVITREAL INJECTION OF AFLIBERCEPT OR BROLUCIZUMAB FOR NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 3 (March 2022) - Angermann, Reinhard; Huber, Anna Lena; Nowosielski, Yvonne; Salcher, Stefan; Gasser, Thomas; Seifarth, Christof; Kralinger, Martina T.; Zehetner, Claus
Abstract : Purpose: To analyze and compare the effects of intravitreal brolucizumab versus aflibercept on systemic vascular endothelial growth factor (VEGF)-A levels in patients with neovascular age-related macular degeneration. Methods: In this prospective interventional case series study, brolucizumab (6.0 mg/50 µ L) or aflibercept (2.0 mg/50 µ L) was injected intravitreally in 30 patients each. Blood samples were drawn at baseline and 7 days and 28 days after the first injection. Systemic VEGF-A levels were measured using enzyme-linked immunosorbent assay. Thirty healthy individuals served as controls. Results: The median baseline systemic VEGF-A levels in the brolucizumab, aflibercept, and control groups were 10.8 (8.0–13.2), 12.0 (8.0–18.5), and 10.0 (8.0–15.1) pg/mL, respectively ( P = 0.315). In the brolucizumab group, VEGF-A levels significantly decreased to 8.0 (8.0–11.5) pg/mL on Day 7 ( P = 0.0254) and to 8.0 (8.0–8.0) pg/mL on Day 28 ( P < 0.001). In the aflibercept group, VEGF-A levels significantly decreased to 8.0 (8.0–8.0) pg/mL on Day 7 ( P < 0.001) but returned to the baseline level, 12.5 (8.5–14.6) pg/mL, on Day 28 ( P = 0.120). Vascular endothelial growth factor–A levels were significantly different between the treatment groups after 28 days ( P < 0.001). Conclusion: Intravitreal brolucizumab resulted in a sustained reduction of systemic VEGF-A levels until 28 days posttreatment, which raises concerns regarding its safety and long-term effects. Abstract : We observed a sustained reduction of systemic VEGF-A in patients receiving intravitreal brolucizumab, with the greatest effect measured 28 days posttreatment. Intravitreal aflibercept also induced a decrease of systemic VEGF-A, but in contrast to brolucizumab, the reduction was less sustained and values returned to baseline within 28 days.